Clinically relevant advances in acne management with adapalene 0.1%/benzoyl peroxide 2.5% gel. (February 2011) - Tan, Jerry; Peermohamed, Shaqil
Adapalene 0.1%/benzoyl peroxide 2.5% (adapalene/BPO) gel is a fixed-dose gel combining a topical retinoid and benzoyl peroxide. It is efficacious in moderate inflammatory acne and the combination provides efficacy greater than the sum of its active components for all relevant outcome measures for acne. In particular, this effect is maximal early in the course of therapy. While there was a range of lesion counts associated with moderate acne severity, adapalene/BPO was of greatest efficacy in those with higher lesion counts. The adjunctive use of adapalene/BPO with oral doxycycline increases the rate of global success fourfold beyond that of oral doxycycline alone. While this agent can be associated with an increased incidence of local intolerability, practical measures to address these issues can maintain patient acceptability.